Draft Annual Plan 2006-07 Volume-I Planning and Development Department Dispur Government of Assam - Planning Commission (Planning Commission, 2006)
Assam, the gateway to the beautiful North Eastern Region of India, today is a State with a mission. The ‘Mission’ is to accomplish accelerated development by overcoming both natural and man made growth barriers. Assam has been eternally blessed with a bountiful nature. The blue mountains with a wide array of fauna and flora; the mighty Brahmaputra and its tributaries providing abundant water resources; the dense forests covering wide range of medicinal plants; the oil and natural gas; the fertile valleys and hill slopes nourishing tea gardens, horticultural crops and vital food grains cumulatively provide immense possibilities for economic development. Assam has been, on the other hand, a victim of history since independence. The partition of the country was a big blow to its socio-economic development.
Planning and Development Department Dispur Government of Assam